Increased Virulence of Bloodstream Over Peripheral Isolates of P. aeruginosa Identified Through Post-transcriptional Regulation of Virulence Factors - Hickey, Caitríona; Schaible, Bettina; Nguyen, Scott; Hurley, Daniel; Srikumar, Shabarinath; Fanning, Séamus; Brown, Eric; Crifo, Bianca; Matallanas, David; McClean, Siobhán; Taylor, Cormac T.; Schaffer, Kirsten (Frontiers in Cellular and Infection Microbiology, 2018)
The factors influencing the virulence of P. aeruginosa in the development of invasive infection remain poorly understood. Here, we investigated the role of the host microenvironment in shaping pathogen virulence and investigated the mechanisms involved. Comparing seven paired genetically indistingushable clinical bloodstream and peripheral isolates of P. aeruginosa, we demonstrate that isolates from bloodstream microenvironments are more virulent compared to their peripheral counterparts (p=0.025). Bloodstream and peripheral isolates elicited similar NF-kB responses in isolated human monocytes implicating similar immunogenicity. However, analysis of the secretome by mass spectrometry identified multiple virulence and virulence-related factors including LecA and RpoN in significantly greater abundance from the bloodstream isolate relative to the peripheral isolate. Investigation by qPCR revealed that control of expression of these virulence factors was not transcriptional. Based on these data, we hypothesize a post-transcriptional mechanism of virulence regulation in P. aeruginosa bloodstream infections influenced by surrounding microenvironmental conditions.